Determinants of democratization explaining regime change in the world, 1972-2006 - Teorell, Jan 1969- (Cambridge University Press, 2010)
What are the determinants of democratization? Do the factors that move countries toward democracy also help them refrain from backsliding toward autocracy? This book attempts to answer these questions through a combination of a statistical analysis of social, economic, and international determinants of regime change in 165 countries around the world in 1972–2006, and case study work on nine episodes of democratization occurring in Argentina, Bolivia, Hungary, Nepal, Peru, the Philippines, South Africa, Turkey, and Uruguay. The findings suggest that democracy is promoted by long-term structural forces such as economic prosperity, but also by peaceful popular uprisings and the institutional setup of authoritarian regimes. In the short-run, however, elite actors may play a key role, particularly through the importance of intra-regime splits. Jan Teorell argues that these results have important repercussions both for current theories of democratization and for the international community's effort in developing policies for democracy promotion